Targeting PP2A with lomitapide suppresses colorectal tumorigenesis through the activation of AMPK/Beclin1-mediated autophagy. (28th November 2021) - Zuo, Qian; Liao, Long; Yao, Zi-Ting; Liu, Ya-Ping; Wang, Ding-Kang; Li, Shu-Jun; Yin, Xing-Feng; He, Qing-Yu; Xu, Wen-Wen
Abstract: Colorectal cancer (CRC) is one of the most common malignancies worldwide, and effective therapy remains a challenge. In this study, we take advantage of a drug repurposing strategy to screen small molecules with novel anticancer activities in a small-molecule library consisting of 1056 FDA-approved drugs. We show, for the first time, that lomitapide, a lipid-lowering agent, exhibits antitumor properties in vitro and in vivo . Activated autophagy is characterized as a key biological process in lomitapide-induced CRC repression. Mechanistically, lomitapide stimulated mitochondrial dysfunction-mediated AMPK activation, resulting in increased AMPK phosphorylation and enhanced Beclin1/Atg14/Vps34 interactions, provoking autophagy induction. Autophagy inhibition or AMPK silencing significantly abrogated lomitapide-induced cell death, indicating the significance of AMPK-regulated autophagy in the antitumor activities of lomitapide. More importantly, PP2A was identified as a direct target of lomitapide by limited proteolysis-mass spectrometry (LiP-SMap), and the bioactivity of lomitapide was attenuated in PP2A-deficient cells, suggesting that the anticancer effect of lomitapide occurs in a PP2A-dependent manner. Taken together, the results of the study reveal that lomitapide can be repositioned as a potential therapeutic drug for CRC treatment. Highlights: Lomitapide screened from FDA-approved drugs induces CRC apoptosis and tumorigenesis inhibition. Lomitapide activates CRC autophagy through inducing AMPK-mediated formation of the Beclin1-Atg14-Vps34 complex. Lomitapide impaires the dephosphorylation of AMPK by directly targeting PP2A.